Suicidal ideation in the perinatal period: findings from the Thailand–Myanmar border. (3rd August 2021) - Fellmeth, G; Nosten, S; Khirikoekkong, N; Oo, M M; Gilder, M E; Plugge, E; Fazel, M; Fitzpatrick, R; McGready, R
Abstract: Background: Suicide is a leading cause of maternal death globally. Migrant and refugee populations may experience higher risk of suicide. We report data on suicidal ideation from migrant and refugee women living on the Thailand–Myanmar border. Methods: Women were recruited in their first trimester of pregnancy. Depression status was assessed by diagnostic interview in the first, second and third trimesters and at 1 month post-partum. We calculated prevalence of suicidal ideation and used logistic regression to identify associated socio-demographic factors. Results: During the perinatal period, 5.3% (30/568) women experienced suicidal ideation. Refugee women were more likely to experience suicidal ideation than migrant women (8.0 versus 3.1%; P = 0.01). Most women with suicidal ideation did not have severe depression. Previous trauma (OR 2.32; 95% CI: 1.70–3.15) and unplanned pregnancy (OR 2.74; 95% CI: 1.10–6.86) were significantly associated with suicidal ideation after controlling for all other variables. Conclusions: Suicidal ideation represents an important symptom among migrant and refugee women on the Thailand–Myanmar border. Screening only those with severe depression may be insufficient to identify women at risk of suicide. Community-level interventions addressing social and gender inequalities and prioritization of family planning programmes are needed alongside targeted suicide prevention initiatives to help lower the rates of people dying by suicide.